Doubling of 30-Day Mortality by 90 Days After Esophagectomy: A Critical Measure of Outcomes for Quality Improvement. Issue 2 (February 2016) - In, Haejin; Palis, Bryan E.; Merkow, Ryan P.; Posner, Mitchell C.; Ferguson, Mark K.; Winchester, David P.; Pezzi, Christopher M.
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: Our objectives were to (1) compare 30- and 90-day mortality rates after esophagectomy, (2) compare drivers of 30- and 90-day mortality, and (3) examine whether 90-day mortality affects hospital rankings. Background: Operative mortality has traditionally been assessed at 30 days. Ninety-day mortality has been suggested as a more appropriate indicator of quality, particularly after complex cancer surgery. Methods: Esophagectomies for nonmetastatic esophageal cancer patients diagnosed between 2007 and 2011 were identified in the National Cancer Data Base. Mortality rates were examined by patient demographics, tumor characteristics, and hospital procedural volume. Risk-adjusted hierarchical logistic regression models examined hospital performance for mortality. Results: A total of 15, 796 esophagectomy patients at 977 hospitals were available for analysis. Ninety-day overall mortality was more than double the 30-day mortality (8.9% vs 4.2%; P < 0.0001). In multivariate analysis, while both 30- and 90-day mortality were associated with patient factors such as age, comorbidity, and hospital volume, only 90-day mortality was influenced by tumor- and management-related variables such as stage, tumor location, and receipt of neoadjuvant therapy. Hospital performance was examined as top 10%, middle 10% to 90%, and lowest 10% as ranked using risk-adjusted odds of mortality. There was moderate correlation between ranking based on 30- and 90-day mortality [weighted κ= 0.45 (95% confidence interval, 0.39–0.52)]. Compared with 30-day mortality rankings, nearly 20% of hospitals changed their ranking category when 90-day mortality rankings were used. Conclusions: Examination of 90-day mortality after esophagectomy reflects cancer patient management decisions and may provide actionable targets for quality improvement.